الصراعات الجيلية في سياق الوسائط الاتصالية الرقمية استخدامات مواقع التواصل الاجتماعي وعلاقات الآباء- الأبناء المراهقين، مقاربة نظرية (مجلة الواحات للبحوث والدراسات, 2022)
ملخص   تهدف هذه الدراسة النّظرية، التّعرض لطبيعة العلاقات النّاشئة بين جيل الآباء وجيل أبنائهم المراهقين الرقميين المستخدمين للوسائط الرقمية والمتمثلة في أكثرها انتشارا بين فئة المراهقين في كل  أنحاء العالم، مواقع شبكات التواصل الاجتماعي وخاصة شبكة الفايسبوك، كشبكات تعيد تراتب ونسج علاقاتهم الاجتماعية القديمة/ الجديدة مع آبائهم وأعضاء أسرهم وأقرانهم، وكيفية تأثيرها على وضعية علاقات الصراع، الانسجام، والسلطة بين الآباء وأبنائهم المراهقين الرقميين، ودور الآباء العِلاقاتي التّنشِأَوي. خلصت الدراسة إلى نتائج أهمها؛ جيل المراهقين المعاصرين يوصف بــــ Digital Native  للإشارة إلى جيل المستخدم الأصلي الذي كبر مع الكمبيوتر والهواتف النقالة والإنترنت، والذي يعكس اختلاف أساسي في التعامل مع التكنولوجيات الاتصالية الحديثة، ويعيشون نمط حياة علاقاتي مختلف عن نمط حياة جيل آبائهم. قضاء أوقات طويلة في فضاءات مواقع التشبيك الاجتماعي، ونزوع المراهقين نحو الاستقلالية وتأكيد ذواتهم عبرها، من شأنه     أن يشكل حركة للصراع الجيلي بين الآباء والأبناء المراهقين نتيجة لتزايد الفجوة الرقمية بين الجيلين. الآباء اليوم هم عرضة للتخلي عن سلطتهم على أبنائهم المراهقين نتيجة لعدم قدرتهم ملاحقة استخداماتهم لتكنولوجيا الاتصال الشبكي وعدم خبرتهم التكنولوجية.كلمات دالة: مواقع التواصل الاجتماعي، المراهقين المعاصرين، الصّراعات الجيليّة، العلاقات الآباء/ الأبناء المراهقين، الخبرة التّكنولوجيّة.  Abstract    The purpose of this theoretical study is to expose the nature of the emerging relationships between the generation of parents and the generation of their digital adolescent children who use digital media, which is the most prevalent among adolescents in all over the world, social media sites, especially Facebook, as networks that reorder and weave their old / new social relationships with their parents, their family members and their peers, and how it affects the status of conflict relationships, harmony, and authority between fathers and their digital adolescent children, and the sculptural relational role of parents. The study concluded with the most important results: The generation of modern teenagers is described as Digital Native to refer to the generation of the original user who grew up with computers, mobile phones and the Internet, which reflects a fundamental difference in dealing with modern communication technologies, and they live a different relationship lifestyle from that of their parents' generation. Spending long time on social media, and the adolescents' tendency towards independence and asserting themselves through it, would constitute a movement of generational conflict between parents and teens children as a result of the growing digital divide between the two generations. Parents today are prone to give up their authority over their adolescent children as a result of their inability to control their use of networking technology and their technological inexperience.Keywords: Social networking sites, modern teens, generational conflicts, parent / adolescent relationships, technological expertise.